EFFECTS OF CURRENT VELOCITY ON FILTRATION AND INGESTION RATE OF PEARL OYSTER (Pinctada maxima) - Apri I. Supii; Dewi Puji Lestari; Sudewi Sudewi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
Pinctada maxima is a filter feeder organism obtaining food particles by filtration from water suspension. Filtration and ingestion rate of a large number of benthic filter feeders in a variety of coastal environment have been known influenced by current velocity. The purposes of this study were to examine the effects of current velocity on filtration and ingestion rate of pearl oyster P. maxima and to determine the best current velocity. Randomized Block Design was used in this experiment with four current treatments of 8, 16, 24, and 32 cm s-1. The results of this experiment demonstrated that current velocity has a marked effect on filtration rate of P. maxima and that this species follows the general pattern of response observed for other bivalves. Different velocity affected filtration and ingestion rate in pearl oyster P. maxima. It was gradual decline in the suspension feeding with increasing velocity. Filtration rate of bivalves with siphons facing into the current, were directly inhibited by hydrodynamic effects on the functioning of the bivalves pump. At increasing current velocity, pressures applied to the inhalant and exhalant aperture facing into the flow would result in higher pressures than that of produced by the ciliary pump, resulting in reduced filtration rate. The highest filtration and ingestion rate in this experiment were obtained at velocity of 8 cm s-1 that achieved 3.409±0.485 l/h and 37.91±1.27 (x107) cells/h, respectively.